HUBUNGAN ANTARA GAYA HIDUP DAN PENGENDALIAN DIRI TERHADAP PERILAKU KONSUMTIF MAHASISWA MELAKUKAN ONLINE SHOPING PADA PRODI BIMBINGAN DAN KONSELING UNIVERSITAS PGRI MAHADEWA INDONESIA TAHUN 2022 - I Nyoman Rajeg Mulyawan; Made Wery Dartiningsih; Ayu Made Nia Mahayani (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
This study aims to determine the relationship between lifestyle and self-control on the consumptive behavior of students doing online shopping at the Guidance and Counseling Study Program, Universitas PGRI Mahadewa Indonesia. This research is an ex post facto research with a sample of 92 people. From the results of the analysis with SPSS, it is found that: there is a strong relationship between lifestyle and self-control on the consumptive behavior of students in doing online shopping, as evidenced in the R squer test, which is 0.861. Lifestyle has a positive influence on consumptive behavior with a value of 0.569. While self-control has a negative effect on consumptive behavior with a value of -0.343. It can be concluded that there is a relationship between lifestyle and self-control on the consumptive behavior of students doing online shopping. Based on the SPSS count value of multiple linear regression test, lifestyle influences the consumptive behavior of students doing online shopping increased by 0.569. This means that lifestyle variables contribute positively to the consumptive behavior of students doing online shopping. self-control affects the consumptive behavior of students doing online shopping activities decreased by 0.343. This shows that the self-control variable contributes negatively to the consumptive behavior of students doing online shopping, so that the higher the self-control of students doing online shopping, the lower the level of students doing consumptive behavior. It is recommended for students to reduce the hedonic lifestyle that tends to make students dependent and result in consumptive behavior